2022
DOI: 10.1093/jmammal/gyac117
|View full text |Cite
|
Sign up to set email alerts
|

To go or not to go: variable density-dependent dispersal in small mammals

Abstract: Population density has been widely understood to be a key influencer of dispersal behavior; however, the generality of density-dependent (DD) dispersal in vertebrates is unclear. We conducted a review of the available empirical data on small mammal DD dispersal, distinguishing between the three dispersal stages: emigration, immigration, and transience (dispersal distance). We focused on small mammals because they are a well-studied, functionally similar group of vertebrates, with a distinct ecological importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
1
1
Order By: Relevance
“…Comparable to a recent review conducted on densitydependent dispersal in small mammals [85], we find that the reported observations on the effect of density on dispersal are limited and do not allow for the comparison or generalization of dispersal behavior across systems, even within taxonomic group. Another recent review reported that during 2009-2018, most studies on animal movement were in relation to external factors, but of those, only 38% were on movement in relation with other animals, conspecific or heterospecific [50].…”
Section: Study Categorycontrasting
confidence: 91%
See 1 more Smart Citation
“…Comparable to a recent review conducted on densitydependent dispersal in small mammals [85], we find that the reported observations on the effect of density on dispersal are limited and do not allow for the comparison or generalization of dispersal behavior across systems, even within taxonomic group. Another recent review reported that during 2009-2018, most studies on animal movement were in relation to external factors, but of those, only 38% were on movement in relation with other animals, conspecific or heterospecific [50].…”
Section: Study Categorycontrasting
confidence: 91%
“…However, there is potential for disparities among the results of different studies to be induced by taxonomic and/or methodological differences. Therefore, and unlike existing reviews on density-dependent dispersal [ 11 , 41 , 61 , 85 ], we particularly examined the extent to which several categories of study methodology, within and across taxonomic groups, impacted empirical results for the effect of density on dispersal. We explicitly considered heterogeneity and potential reporting of analytical biases, and tested whether reports of density-dependent dispersal were related to taxonomic group, sex, age, migratory behavior, study design, dispersal metric, density metric and variable type, and scales of space and time.…”
Section: Introductionmentioning
confidence: 99%